Clinical outcome of narrow diameter implants inserted into allografts - Maurizio Franco; Alessandro Viscioni; Leone Rigo; Riccardo Guidi; Ilaria Zollino; Anna Avantaggiato; Francesco Carinci (University of São Paulo, 2009)
OBJECTIVE: Narrow diameter implants (NDI) (i.e. diameter <3.75 mm) are a potential solution for specific clinical situations, such as reduced interradicular bone, thin alveolar crest and replacement of teeth with small cervical diameter. NDI have been available in clinical practice since the 1990s, but only few studies have analyzed their clinical outcome and no study have investigated NDI inserted in fresh-frozen bone (FFB) grafts. Thus, a retrospective study on a series of NDI placed in homologue FFB was designed to evaluate their clinical outcome. MATERIAL AND METHODS: In the period between December 2003 and December 2006, 36 patients (22 females and 14 males, mean age 53 years) with FFB grafts were selected and 94 different NDI were inserted. The mean follow-up was 25 months. To evaluate the effect of several host-, surgery-, and implant-related factors, marginal bone loss (MBL) was considered an indicator of success rate (SCR). The Kaplan Meier algorithm and Cox regression were used. RESULTS: Only 5 out of 94 implants were lost (i.e. survival rate - SVR 95.7%) and no differences were detected among the studied variables. On the contrary, the Cox regression showed that the graft site (i.e. maxilla) reduced MBL. CONCLUSIONS: NDI inserted in FFB have a high SVR and SCR similar to those reported in previous studies on regular and NDI inserted in non-grafted jaws. Homologue FFB is a valuable material in the insertion of NDI.